2011
DOI: 10.1093/icc/dtq069
|View full text |Cite
|
Sign up to set email alerts
|

Balancing specialized and generic capabilities in the provision of integrated solutions

Abstract: Integrated bundles of products and services are gaining importance in various sectors and are reshaping the competitive landscape of many industries. They also pose new challenges to established firms, who need to reconfigure their capabilities. Drawing upon the resource-based view and contingency theory, we test a model of fit between environmental requirements and integrated solutions capabilities in the IT sector. We used the model to interpret the current industry structure and analyze its dynamics. The an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(72 citation statements)
references
References 64 publications
2
70
0
Order By: Relevance
“…On the one hand, our study continues to build on the growing interest in studying cross-border and cross-sector strategic alliances (Gomes et al, 2016;Lew & Sinkovics, 2013;Luo, Wang, Jayaraman, & Zheng, 2013). On the other, it is amongst the first articles to study how the service function can be externalized through alliances (Bustinza et al, 2017a;Ceci & Masini, 2011;Durugbo & Erkoyuncu, 2016) or mergers and acquisitions (Xing et al, 2017) and to investigate the importance of expertise decision centralization in enhancing service-led growth strategies (Ghosh, 2013;Johnstone et al, 2014;Prajogo & Oke, 2016). More importantly, based on a unique survey-based sample of 285 MMNEs with head offices in the US, China, Germany, Japan and the UK, this study is, to the best of our knowledge, the first to investigate the innovation outcome of service-unit internationalization.…”
Section: Theoretical Implicationsmentioning
confidence: 93%
See 2 more Smart Citations
“…On the one hand, our study continues to build on the growing interest in studying cross-border and cross-sector strategic alliances (Gomes et al, 2016;Lew & Sinkovics, 2013;Luo, Wang, Jayaraman, & Zheng, 2013). On the other, it is amongst the first articles to study how the service function can be externalized through alliances (Bustinza et al, 2017a;Ceci & Masini, 2011;Durugbo & Erkoyuncu, 2016) or mergers and acquisitions (Xing et al, 2017) and to investigate the importance of expertise decision centralization in enhancing service-led growth strategies (Ghosh, 2013;Johnstone et al, 2014;Prajogo & Oke, 2016). More importantly, based on a unique survey-based sample of 285 MMNEs with head offices in the US, China, Germany, Japan and the UK, this study is, to the best of our knowledge, the first to investigate the innovation outcome of service-unit internationalization.…”
Section: Theoretical Implicationsmentioning
confidence: 93%
“…This is especially true for MMNEs, which are assumed to have enough internal resources to undertake this function internally (Visnjic, Jovanovic, Neely, & Engwall, 2017;Woerkom & Zeijl-Rozema, 2017). The first research considering a different strategic option was undertaken by Ceci and Masini (2011), who found that half of manufacturers work in partnerships with software firms to enhance and customize their products. This result was extended by Paiola et al (2013), who analysed the 'make or buy' decision of service capabilities.…”
Section: Geographical Location and Ownership Of The Service Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Coping strategies involve conforming through mimicking, professionalization and formalization or avoidance of a specific segment altogether (Suchman, 1995). These strategies can be costly, difficult to implement or dilute the newness of the innovation under development (Ceci & Masini, 2011). Collaboration with a legitimate partner for that segment can be an effective way to overcome this liability.…”
Section: Market Heterogeneitymentioning
confidence: 99%
“…[8,2]. Overcoming this hitchreferred to as the servitization paradox in the literature [9] -represents a major managerial challenge: companies need to re-design their organisational principles, structures, processes [8], capabilities [10], as well as the relationships with customers [11] and suppliers [12]. Indeed, the design and development of a PSS raise new issues; the service component introduces new requirements that are less (or not at all) relevant in a traditional, product-based business model.…”
Section: Introductionmentioning
confidence: 99%